SIGN LANGUAGE LITERACY IN THE SIGN LANGUAGE CURRICULUM - Mertzani, Maria (Momento - Diálogos em Educação, 2022)
The Sign Language curriculum is a contemporary development which few countries have officially implemented to teach a national standard Sign Language as a first language (L1) and/or mother tongue in the school grades. In these, Sign Language is a mandatory unit, which the deaf child needs to study and develop metalinguistically, as is the case in learning spoken languages as L1. A Sign Language as a metalanguage also means that the curriculum teaches explicit linguistic knowledge for the child to understand gradually how SL functions in different contexts, to make effective choices for meaning or style, and to comprehend more fully when attending the language. In other words, the Sign Language curriculum addresses the importance of developing the child’s Sign Language literacy. Traditionally, literacy is linked to reading and writing and for its learning the language curriculum sets five essential early literacy components: comprehension, phonological awareness, phonics, print convention knowledge and fluency. The paper discusses these components in support of Sign Language literacy as a verbal (non-print) form of literacy, based on a documental study among the Sign Language and indigenous curriculum.